2009
DOI: 10.4028/www.scientific.net/amr.79-82.1391
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Test and Numerical Analysis of Structural Steel Notched Plates Based on Generalized Strength Model

Abstract: To study rupture mechanism of structural steel, fracture experiments were tested on 12 notched plates with different thickness. The results of experiments indicated that the first crack initiated at the notched edge and expanded rapidly along the width of the plates after running through the thickness. Finally, the specimens fractured at the critical section, the fracture ductility decreased with the thickness. By numerically simulating the fracture stress field of the notched plates at initial cracking based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The parameters ôy, óy, óseq and óm denote the material's equivalent shear yield strength, uniaxial yield strength, Mises equivalent stress and mean stress, respectively. Based on the observed fact that the fracture strain for metals decreases as the stress triaxiality ratio (óm/óseq) increases and the supposition that the fracture strain for metals reaches the minimum value when the material is subjected to equal stresses in the three principal directions, or óm/óseq=∞, an elliptical fracture model is also proposed for structural steels Wang, 2008;Wang et al, 2009;Wang et al, 2010] as shown in Eq. ( 2).…”
Section: An Elliptical Yield Model and Ellipitical Fracture Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters ôy, óy, óseq and óm denote the material's equivalent shear yield strength, uniaxial yield strength, Mises equivalent stress and mean stress, respectively. Based on the observed fact that the fracture strain for metals decreases as the stress triaxiality ratio (óm/óseq) increases and the supposition that the fracture strain for metals reaches the minimum value when the material is subjected to equal stresses in the three principal directions, or óm/óseq=∞, an elliptical fracture model is also proposed for structural steels Wang, 2008;Wang et al, 2009;Wang et al, 2010] as shown in Eq. ( 2).…”
Section: An Elliptical Yield Model and Ellipitical Fracture Modelmentioning
confidence: 99%
“…This study investigates the fracture behavior of notched tension bars through an experimental program consisting of 20 specimens with different notch geometries. The numerical analysis implements an elliptical yield model Wang, 2008;Wang et al, 2009;Wang et al, 2010] to simulate the effect of the high hydrostatic stresses on the material yield response. The experimental fracture failure is then further compared with the proposed elliptical fracture model Wang, 2008;Wang et al, 2009;Wang et al, 2010], which depends both on the effective stress and the mean stress.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have carried out on metal crack [Bao, 2005;Hancock and Mackenzie, 1976;Joribio, 1997;Wang, 2007;Wang, 2008;Wang et al, 2009;Wang et al, 2010], but there is no effective method to avoid brittle fracture of constructional steel. Bridging between the theoretical development and the engineering practice, therefore, still remains a critical challenge to the academic and engineering profession.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have carried out on metal crack [3][4][5][6][7][8][9][10], but there is no effective method to avoid brittle fracture of constructional steel. Bridging between the theoretical development and the engineering practice, therefore, still remains a critical challenge to the academic and engineering profession.…”
Section: Introductionmentioning
confidence: 99%